TINJAUAN YURIDIS TERHADAP AKTA NOTARIS DALAM TRANSAKSI ELEKTRONIK (suatu wacana) - , Hijah Aulia Marta, Dwi Haryati, S.H, M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research concern on juridical review of the notarial deed in electronic transaction (a discourse). Aims to find out that the conventional notarial deed can be form into electronic notarial deed which has strong legal evidence as authentic notarial deed and to understand concept of application notarial deed in electronic form which recognize as authentic notarial deed in the future. This research is used normative juridical data. Method of data collecting is collect the law material by documentation. This documentation method doing with collecting law material from article which consist primary law material, secondary law material, and tertiary law material. This research also consist of law material from library research, rule of ordinance, and concerned articles. Which elaborate and connect by the author. The result were analyzed and apply more systematic to answer the problem statement. Grounded on this research, we can conclude that the notarial deed with electronic form still admit as low approvement notarial deed, because authentic notarial deed is made by notary which form and characteristic of the notarial deed it must be appropriate with the legislation. If refers to information and electronic transaction constitution. Electronic notarial deed has a chance to admit as authentic notarial deed. Moreover if it consider with an evidence. In this case the electronic deed and the electronic signature. Can be admit as authentic deed. And also will be admit as a authentic notarial deed which has a strong legal evidence. Notary official deed application concept in electronic form in the future by revision of constitution no. 30 of 2004. And also there will be addition of the article said that the authentic notarial deed can be done in electronic form or through the virtual world with addition that the notarial deed can be read by the notary, heard and shown by the audience online.